2018
DOI: 10.1002/2017jg004199
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification in Shallow Groundwater Below Different Arable Land Systems in a High Nitrogen‐Loading Region

Abstract: To evaluate the risk of nitrate (NO3−‐N) in groundwater, it is necessary to know the denitrification capacity. In this study, observations were carried out for 2 years to investigate the groundwater denitrification capacity below three arable land systems in eastern China. Denitrification capacity was assessed by measuring the concentration and distribution patterns of nitrous oxide (N2O) and dinitrogen (N2) in groundwater. The results revealed that groundwater denitrification activity was high and consumed 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 62 publications
(97 reference statements)
1
4
0
Order By: Relevance
“…Application of 0-150 kg/ha N at the 60-90 cm depth may be insufficient, which was manifested as nutrient deficiency (Figure 5), as similar to previous conclusion [52]. In our results, 240-300 kg/ha N application can effectively replenish the soil vadose zone system, making up for nitrogen loss, such as high-intensity denitrification, leaching and dissolving under high groundwater table, as depicted previously [44,64,70], which may promote crop growth. Additionally, 150-240 kg/ha N application was moderate and could promote crop yields at a depth of 90-150 cm (Table 3).…”
Section: Soil Water and Nitrogen Storagesupporting
confidence: 90%
“…Application of 0-150 kg/ha N at the 60-90 cm depth may be insufficient, which was manifested as nutrient deficiency (Figure 5), as similar to previous conclusion [52]. In our results, 240-300 kg/ha N application can effectively replenish the soil vadose zone system, making up for nitrogen loss, such as high-intensity denitrification, leaching and dissolving under high groundwater table, as depicted previously [44,64,70], which may promote crop growth. Additionally, 150-240 kg/ha N application was moderate and could promote crop yields at a depth of 90-150 cm (Table 3).…”
Section: Soil Water and Nitrogen Storagesupporting
confidence: 90%
“…In the model, the N 2 O possibly produced via nitrification in groundwater is assumed to be consumed during transport, thus not reaching surface waters. Based on refs , , and Figure S5, a constant fraction ( f N 2 O_sgrw = 1%, median of the 278 reported measurement-based values; see Text S1 for details) of shallow groundwater denitrification (DENIT sgrw ) , is calculated as the associated net N 2 O production (i.e., L N 2 O_grw_sgrw , part i), which is transported to surface waters directly or indirectly via deep groundwater or riparian zones (Figure S4), following eq normalL normalN 2 normalO normal_ grw normal_ sgrw = DENI T sgrw · f normalN 2 normalO normal_ sgrw …”
Section: Methodsmentioning
confidence: 99%
“…A study of the hilly area in southern China also found that orchards (with vadose zone thicknesses > 4 m) have high nitrate accumulation in soil, and the nitrate accumulation increases with the vadose zone thickness [37] . Therefore, overuse of N fertilizer, a thick vadose zone, strong soil nitrification and weak denitrification (from low soluble organic carbon content and good aeration) may explain why high nitrate accumulation is found in the vadose zones of intensive planting areas in China [5,6,10,38] .…”
Section: Fate Of Nitrogen In Intensive Orchards and Vegetable Fieldsmentioning
confidence: 99%